2017
DOI: 10.3390/app8010004
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Dissolution Rate of CO2-Brine in Porous Media under Gaseous and Supercritical Conditions

Abstract: Abstract:The CO 2 -brine dissolution homogenizes the distribution of residual CO 2 and reduces the leakage risk in the saline aquifer. As a key parameter to immobilize the free CO 2 , the dissolution rate of CO 2 -brine could be accelerated through mechanisms like diffusion and dispersion, which are affected by the subsurface condition, pore structure, and background hydrological flow. This study contributed the calculated dissolution rates of both gaseous and supercritical CO 2 during brine imbibition at a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Wu et al. (2018) also conducted gaseous/supercritical CO 2 dissolution in brine and observed the scCO 2 flow and dissolution in 2D images. Based on advanced microfluidic techniques, Chang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al. (2018) also conducted gaseous/supercritical CO 2 dissolution in brine and observed the scCO 2 flow and dissolution in 2D images. Based on advanced microfluidic techniques, Chang et al.…”
Section: Introductionmentioning
confidence: 99%
“…L. Jiang et al (2018) investigated the dynamic displacement and gaseous/supercritical CO 2 dissolution under different temperature/pressure conditions and analyzed the relationship between dissolution rate and flow rate. Wu et al (2018) also conducted gaseous/supercritical CO 2 dissolution in brine and observed the scCO 2 flow and dissolution in 2D images. Based on advanced microfluidic techniques, Chang et al (2016Chang et al ( , 2017 conducted scCO 2 imbibition/drainage and dissolution experiments at pore-scale in 2D heterogeneous sandstone micromodels and found water-flow paths and scCO 2 nonuniform dissolution were strongly correlated.…”
mentioning
confidence: 99%
“…Macroscopic modelling of fluid reaction and transport in porous media also requires finding the model that can accurately describes the average porescale conditions (Battiato et al 2009, Battiato andTartakovsky 2011). For applications related to carbon sequestration study, precise measurements of water-CO 2 interfacial area contributes to the investigation of the mass transfer coefficients of CO 2 (Miller et al 1990;Wu et al 2017;Patmonoaji and Suekane 2017). Accurate measurements of interfacial area can also be useful for obtaining estimates of in-situ contact angles under the thermal equilibrium assumption (Blunt et al, 2019), and directly discerning wettability state (Garfi et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%